Phylogeography and Pleistocene refugia of the Little Owl Athene noctua inferred from mtDNA sequence data. (14th May 2014) - Pellegrino, Irene; Negri, Alessandro; Cucco, Marco; Mucci, Nadia; Pavia, Marco; Šálek, Martin; Boano, Giovanni; Randi, Ettore; Fuchs, Jerome
<x xml:space="preserve">Abstract</x> Pleistocene glaciations greatly affected the distribution of genetic diversity in animal populations. The Little Owl is widely distributed in temperate regions and could have survived the last glaciations in southern refugia. To describe the phylogeographical structure of European populations, we sequenced the mitochondrial cytochrome c oxidase I (COI) and control region (CR1) in 326 individuals sampled from 22 locations. Phylogenetic analyses of COI identified two deeply divergent clades: a western haplogroup distributed in western and northwestern Europe, and an eastern haplogroup distributed in southeastern Europe. Faster evolving CR1 sequences supported the divergence between these two main clades, and identified three subgroups within the eastern clade: Balkan, southern Italian and Sardinian. Divergence times estimated from COI with fossil calibrations indicate that the western and eastern haplogroups split 2.01–1.71 Mya. Slightly different times for splits were found using the standard 2% rate and 7.3% mtDNA neutral substitution rate. CR1 sequences dated the origin of endemic Sardinian haplotypes at 1.04–0.26 Mya and the split between southern Italian and Balkan haplogroups at 0.72–0.21 Mya, coincident with the onset of two Pleistocene glaciations. Admixture of mtDNA haplotypes was detected in northern Italy and in central Europe. These findings support a model of southern Mediterranean and Balkan refugia, with postglacial expansion and secondary contacts for Little Owl populations. Central and northern Europe was predominantly recolonized by Little Owls from Iberia, whereas expansion out of the Balkans was more limited. Northward expansion of the Italian haplogroup was probably prevented by the Alps, and the Sardinian haplotypes remained confined to the island. Results showed a clear genetic pattern differentiating putative subspecies. Genetic distances between haplogroups were comparable with those recorded between different avian species.